The future of work : attract new talent, build better leaders, and create a competitive organization - Morgan, Jacob (New York John Wiley and Sons, 2014)
"​Throughout the history of business employees had to adapt to managers and managers had to adapt to organizations. In the future this is reversed with managers and organizations adapting to employees. This means that in order to succeed and thrive, organizations must rethink and challenge everything they know about work. The demographics of employees are changing and so are employee expectations, values, attitudes, and styles of working. Conventional management models must be replaced with leadership approaches adapted to the future employee. Organizations must also rethink their traditional structure, how they empower employees, and what they need to do to remain competitive in a rapidly changing world. This is a book about how employees of the future will work, how managers will lead, and what organizations of the future will look like". Publisher's website
​Introduction: rethinking chess and work -- 1 The Five trends shaping the world of work -- 2 The Cog: today's employee -- 3 Seven Principles of the future employee -- 4 The Freelancer economy -- 5 The Zookeeper: today's manager -- 6 Ten Principles of the future manager -- 7 The Managerless company -- 8 The Organization of today -- 9 Fourteen principles of the future organization -- 10 Technology as the central nervous system -- 11 The Six-step process for adapting to the future of work: how to become the future organization (and stay that way!) -- 12 Rethinking work --
Includes bibliographical references (P:217-221) and index.
Keywords: Executive management; EXECUTIVE MANAGEMENT; ECONOMIC PLANNING; CORPORATE PLANNING; ORGANIZATIONAL PLANNING; LEADERSHIP